Tolerability of proactive enteral nutrition post allogeneic haematopoietic progenitor cell transplant: A randomised comparison to standard care. Issue 5 (May 2020) - Andersen, Sarah; Weber, Nicholas; Kennedy, Glen; Brown, Teresa; Banks, Merrilyn; Bauer, Judy
Summary: Background & aims: Nutrition support is an important component of care to prevent malnutrition during allogeneic haematopoietic progenitor cell transplantation (HPCT) however there is no consensus on the optimal method of nutrition support. It is currently unclear whether enteral nutrition (EN) via nasogastric (NG) feeding is tolerated and improves clinical outcomes in comparison with parenteral nutrition (PN). This randomised study aimed to determine the tolerability and outcomes of proactive EN in comparison to PN (standard care). Methods: Patients aged ≥18 years undergoing allogeneic transplantation with reduced intensity (fludarabine/melphalan) or myeloablative (cyclophosphamide/TBI) conditioning at a tertiary Australian hospital were eligible to participate. Patients were recruited pre-transplant and randomised to proactive enteral nutrition (EN) or standard care. The EN group underwent NG tube insertion the day after stem cell infusion with feeding commenced at 30 ml/h. Rate of feeding was increased to goal as oral intake declined. If patients were intolerant to NG feeding they were changed to PN if required. The standard care group commenced PN when oral intake was ≤60% of requirements for three days and was unlikely to improve for at least another week as per standard unit protocol. The primary endpoint was tolerance of EN. Results: Forty-four patients, (median age [Q1–Q3]: 52 [38–59], 25 male, 19 female) were recruited and randomised to EN (n = 22) or standard care (n = 22). In the EN group eleven tolerated EN (55%), nine changed to PN and two withdrew from study. The median (Q1–Q3) duration of NG feeding was nine days (4–13) and this provided 86% of goal nutrition. In the standard care group 68% required PN, the median duration was nine days (0–17) and patients met 97% of goal nutrition. There were no statistically significant differences between groups for any clinical outcomes or grade 3–4 (CTCAE version 4) complications. Conclusions: Half of patients receiving allogeneic transplantation tolerate EN when commenced early post-conditioning. As the use of proactive EN will reduce the use of PN (and associated costs and risks), it should be considered first line nutritional support. Registration: This trial was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) trial number ACTRN12615000284561.